1998
DOI: 10.1021/ja972620e
|View full text |Cite
|
Sign up to set email alerts
|

Topological Analysis of the Experimental Electron Densities of Amino Acids. 1.d,l-Aspartic Acid at 20 K

Abstract: High-resolution X-ray diffraction data collected at 20 K are interpreted in terms of the rigid-pseudoatom formalism to derive the electron density and related properties, such as the electrostatic potential and electric moments, of the crystalline d,l-aspartic acid. The refinement models applied are restricted via rigid-bond type constraints to reduce possible bias in the mean-square displacement amplitudes due to inadequacies in the thermal deconvolution. The density and its Laplacian extracted from the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
84
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 35 publications
16
84
0
4
Order By: Relevance
“…The topology of such densities can also be analysed using the theory of atoms in molecules (AIM) (Bader, 1990). A variety of such studies has been published, ranging from the relatively simple NH 3 molecule (Boese et al, 1997) to more complex organic molecules (Flaig et al, 1998;Souhassou & Blessing, 1999;Koritsa  nszky et al, 1999Koritsa  nszky et al, , 2000, and transition-metal complexes (Smith et al, 1997;Iversen et al, 1997;Macchi et al, 1998a,b;Bianchi et al, 2000;Bytheway et al, 2001) as well as the bulk crystalline phase of SiO 2 (Rosso et al, 1999) and Cu 2 O (Lippmann & Schneider, 2000). Analysis of charge densities using the theory of AIM is appealing since it provides de®nitions of atoms and bonds that depend only on the charge density, not upon the method by which it was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The topology of such densities can also be analysed using the theory of atoms in molecules (AIM) (Bader, 1990). A variety of such studies has been published, ranging from the relatively simple NH 3 molecule (Boese et al, 1997) to more complex organic molecules (Flaig et al, 1998;Souhassou & Blessing, 1999;Koritsa  nszky et al, 1999Koritsa  nszky et al, , 2000, and transition-metal complexes (Smith et al, 1997;Iversen et al, 1997;Macchi et al, 1998a,b;Bianchi et al, 2000;Bytheway et al, 2001) as well as the bulk crystalline phase of SiO 2 (Rosso et al, 1999) and Cu 2 O (Lippmann & Schneider, 2000). Analysis of charge densities using the theory of AIM is appealing since it provides de®nitions of atoms and bonds that depend only on the charge density, not upon the method by which it was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a measurement at 20 K (Flaig et al 1998) and a refinement of data gathered with neutron diffraction data (Sequeira et al 1989) were also reported.…”
Section: Aspartic Acidmentioning
confidence: 99%
“…To evaluate the atomic volumes and charges the program TOPXD [4] was used.In order to examine the transferabillity of smaller fragments the topology of submolecular parts of the three molecules were compared with each other and with those of the Matta study.[1] Matta C.F., J. Phys. Chem., 2001 Nucleosides play a key role in life.…”
mentioning
confidence: 99%
“…From our investigation, we have discovered an E2 RXS feature, for which the azimuth dependence can be reconciled with an ordered octupole moment in phase IV. The results give, to our knowledge, the first direct evidence for a new order parameter in the Ce 0.7 La 0.3 B 6 ground.[ To answer the title question we computed for a variety of small molecules hydrogen ADPs as described in [4], implemented in the XD [5] suite. In that procedure the internal displacements for all atoms are calculated by an ab initio methods, and then subtracted from the experimental data that also contain the external modes.…”
mentioning
confidence: 99%
See 1 more Smart Citation